Gewalt in Adelsehen zur Barockzeit: Causa Karl Adam von Mansfeld (Theatrum historiae, 2012)
The submitted work deals with marriage disputes of the aristocracy of the Czech lands in the second half of the 17th century, where there was a certain effort by noblewomen to change the relationship and arrangement of power in marriage and disputes between husband and wife were on the rise. First it focuses on the question of what function marriage had in the aristocracy and what roles, according to the norms of the time, were played by men and especially by women. It interests me how the matters of distribution of power between husband and wife were perceived by society in the light of the existing rules and what everyday practise was like. Because in the case I look at in greater detail in this work, violence played a great role, I will also concentrate on the theory of violence in unions of marriage of the period. The main part of my work is made up of a reconstruction of the legal case concerning the tragic demise of Maria Terezia Mansfeld of Dietrichstein, of which Karl Adam of Mansfeld was accused. The conclusion will deal with a comparison of this case with the dispute that arose in the Kaunitz family.
Keywords: Aristocratic marriage; early modern times; gender history; Czech lands; marriage disputes; violence in marriage; the Mansfeld family; the Dietrichstein family